2002
DOI: 10.1093/treephys/22.10.699
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange, biomass, whole-plant water-use efficiency and water uptake of peach (Prunus persica) seedlings in response to elevated carbon dioxide concentration and water availability

Abstract: We examined the interactive effects of elevated CO2 concentration ([CO2]) and water stress on growth and physiology of 1-year-old peach (Prunus persica L.) seedlings grown in 10-dm3 pots in open-top chambers with ambient (350 micromol mol-1) or elevated (700 micromol mol-1) [CO2]. Seedlings were supplied weekly with a non-limiting nutrient solution. Water was withheld from half of the plants in each treatment for a 4-week drying cycle, to simulate a sudden and severe water stress during the phase of rapid plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 20 publications
4
29
1
1
Order By: Relevance
“…Decreased N concentration can also be due to lower specific leaf area in elevated CO 2 (Centritto et al 2002). Leaf nitrogen and some proteins decrease in leaves exposed to high CO 2 (Rogers et al 1996, Uprety et al 2002, Moynul Haque et al 2006.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Decreased N concentration can also be due to lower specific leaf area in elevated CO 2 (Centritto et al 2002). Leaf nitrogen and some proteins decrease in leaves exposed to high CO 2 (Rogers et al 1996, Uprety et al 2002, Moynul Haque et al 2006.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…A second limitation is the possible effect of elevated CO 2 on stomatal conductance, resulting in reduced transpiration and demand for water (Drake et al 1997). Although there is little direct, experimental evidence that fruit trees display reduced transpiration in response to elevated CO 2 (Centritto et al 1999(Centritto et al , 2002, there is considerable evidence that grasses and other annual C3 crops transpire less in elevated CO 2 atmospheres (Morison 2001). Such reductions in water demand may be as high as 20-30%, although a study of potential effects of climate change on US agriculture determined that un-irrigated field crops (corn, wheat, alfalfa) grown in the Pacific Northwest and western mountainous regions had relatively low decreases in transpiration by the end of the current century (approximately 8%) compared with other regions (Izaurralde et al 2003).…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Plant growth relies on photosynthesis which utilizes atmospheric CO 2 as substrate. Elevated CO 2 level in the atmosphere therefore is expected to enhance photosynthesis, which in turn increase growth rates and yields of crops, and change morphological-physiological characteristics of crops (Cardoso-Vilhena 2001;Centritto et al 2002;Drake and Gonzàlez-Meler 1997;Raven et al 2004). An extensive review on FACE investigations over the past 15 years (Ainsworth and Long 2005) showed that elevated CO 2 would increase plant biomass to a significant level.…”
Section: Introductionmentioning
confidence: 99%